An ethnographic approach to school convivencia - Cristina Perales Franco (Universidade Federal do Rio Grande do Sul, 2018)
Convivencia is a Spanish concept that addresses the ways of living together, living with others. School convivencia in particular is formed by the tapestry of social relations that construct the everyday life in schools, and it provides the relational elements and boundaries where the school experience is constructed. This article derives from an investigation of the relationships between two Mexican primary schools and their local communities and their implications for school convivencia. It presents two challenges of analysing school convivencia from an ethnographic perspective: the struggle between restrictive and comprehensive approaches and the tension between the specific and the complex in understanding convivencia.